Pengaruh Motivasi dan Minat Belajar Mahasiswa Terhadap Prestasi Belajar Pengantar Ilmu Ekonomi Pada Mahasiswa Jurusan Sistem Informasi Semester 1 STMIK Pranata Indonesia Bekasi - Florentina Risnu Sawitri (Lembaga Pengabdian Masyarakat Universitas Ichsan Gorontalo, 2025)
The purpose of this study is to determine the influence of student motivation and interest in learning on learning achievement Introduction to Economics 1st semester students of STMIK Pranata Indonesia Bekasi Odd Semester 2021/2022 Department of Information Systems with survey research methods. Student research respondents totaled 40 people, selected based on purpose sampling techniques. The instrument uses questionnaires to obtain data on motivation and interest in learning, while learning achievement Introduction to Economics is obtained from the average score of the first semester of the 2021/2022 academic year The method in this study is a survey. There is a significant influence of motivation and interest in learning together on learning achievement Introduction to Economics Students of STMIK Pranata Indonesia Bekasi. That there is a change in the dependent variable, which is 34.7% and the remaining 65.3% which is influenced by variables other than variables X1 and X2 Because the value of F = 7.171 is used to test the hypothesis in predicting the contribution of independent variables (X1 and X2) to the dependent variable (Y)